[PP.22.09] RENAL NATRIURETRIC SYSTEMS ALTERATION IN FRUCTOSE-OVERLOADED HYPERTENSIVE RATS. (September 2016) - Puyó, A.; Kouyoumdzian, N.M.; Mikusic, N.M. Rukavina; Rouvier, E.; Cantú, S.M.; Lee, H.J.; Toblli, J.E.; Fernández, B.E.; Choi, M.R.
Abstract : Objective: Metabolic and hemodynamic changes induced by a high fructose diet could be associated with an impairment of renal natriuretic systems, which contributes to sodium retention and hypertension. There is little evidence about renal dopamine (DA) and type-A natriuretic peptide (ANP) interaction on blood pressure elevation in this model. The aim of this study was to evaluate both natriuretic systems in fructose-overloaded rats. Design and method: Male Sprague Dawley rats were randomly assigned: a) Controls (C, tap water to drink) and b) Fructose overloaded: (F, 10% w/v of fructose to drink), treated during 4, 8 and 12 weeks (n = 8 rats/group/period). Urinary L-dopa and DA (HPLC); diuresis, creatinine and sodium were measured in 24 hour urine samples; and ANP (ELISA), triglycerides, glycemia, cholesterol, insulinemia, creatinine and sodium in plasma. Systolic blood pressure (SBP) was determined by tail-cuff and renal tissue protein expression of L-dopa transporter (LAT-2), D1R and NPR-A receptors by Western blot. Results: Fructose overload increased SBP (mmHg, C4: 121 ± 8 vs. F4: 145 ± 1*; C8: 130 ± 4 vs. F8: 161 ± 10#; C12: 133 ± 5 vs. F12: 163 ± 4#), which positively correlated (R2 = 0.78; p < 0.002) to urinary L-dopa/DA index (C4: 0.49 ± 0.05 vs. F4: 1.9 ± 0.09#; C8: 0.53 ± 0.06 vs. F8: 2.35 ± 0.10#; C12: 0.54 ± 0.07 vs. F12: 2.57 ± 0.20#). An elevation in cortex LAT-2 expression (arbitrary units) (C4: 1.00 ± 0.02 vs. F4: 1.30 ± 0.04*; C8: 1.00 ± 0.05 vs. F8: 1.23 ± 0.09*; C12: 1.00 ± 0.06 vs. F12: 1.40 ± 0.01*) and medulla (C8: 1.00 ± 0.01 vs. F8: 1.42 ± 0.02*; C12: 1.00 ± 0.01 vs. F12: 1.46 ± 0.04*); and a decrease D1R in cortex (C4: 1.00 ± 0.05 vs. F4: 0.72 ± 0.08*; C8: 1.00 ± 0.05 vs. F8: 0.75 ± 0.07*) were found. Plasma ANP decrease (ng/ml: C8: 1.61 ± 0.10 vs. F8: 1.30 ± 0.08*; C12: 1.65 ± 0.32 vs. F12: 1.04 ± 0.16*) along with a lower NPR-A expression in medulla (C4: 1.00 ± 0.05 vs. F4: 0.81 ± 0.02*; C8: 1.00 ± 0.04 vs. F8: 0.80 ± 0.03*; C12: 1.00 ± 0.03 vs. F12: 0.81 ± 0.01*) were also observed (*p < 0.05, #p < 0.01 vs. C). Conclusions: Fructose overload leads to an increase in the urinary L-dopa/DA index from 4th week of treatment that correlates positively with blood pressure elevation. Furthermore the decrease in the natriuretic systems DA and ANP seems to be related to the physiopathology of hypertension in this model.